Kajian Dampak Tiktok Pada Siswa Sekolah Dasar: Kelebihan, Kekurangan, Dan Implikasi Pendidikan - Nur Amalia; Naufal Nafi'ardina (Elementary Teacher Education Program, Majalengka University, 2024)
TikTok app is a video-based online social media application with interesting special effects designed to interest many people, especially children. These elementary school kids love to play, and the playful nature of children makes them interested in the tiktok app and its features. The purpose of the study was to assess the advantages, disadvantages and implication of the tiktok application for elementary school students in Krikilan 1, Kec. Kab, Kalijambe Sragen, Prov. Southeast Java qualitative research, also known as field research , requires interviews and observation of respondents or actors. Children, class teachers, and parents of SD Krikilan 1 were used as research subjects. Utilizing observation and interview methods for data collection, data reduction, data presentation, and conclusion drawing are the three parts of the data analysis method used. According to research findings, the most popular TikTok app content for children aged 6 to 8 years is about challenges, food, cuisine, even student idols such as Ibnu wardani and Fuji. The average use of the tiktok application ranges from 30 minutes to 2 hours. The tiktok app has both positive and negative impacts on children who are 6 to 8 years old. The bad result is that children lose interest in learning, while the positive result is that it can foster and develop creativity and help children develop their skills in video editing.